Formation of Chinese research competence master’s degree students in Russian studies in the context of internationalization of education (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Higher education institutions in China set enhancing research competence as their important goal in postgraduate studies. On the background of continuous economic globalization, internationalization of higher education has become irreversible, and China gradually follows this trend. Strengthening the research and innovation abilities of students requires certain efforts on behalf of educators including the creation of comfortable research environment, promotion of mutual learning and positive initiative, and application of a variety of teaching methods to stimulate students’ in scientific research and help them benefit from it as early as possible. Drawing from the analysis of common problems in the development of postgraduate training schools in China, this paper employs several perspectives to explore the strategies of increasing research and innovation competencies of Master in the Russian Language students and to provide a relevant guidance for educators.
Keywords: internationalisation of higher education, Master in the Russian Language, research competence